2021
DOI: 10.7717/peerj.10728
|View full text |Cite
|
Sign up to set email alerts
|

Consistency of dark skeletal muscles in Thai native black-bone chickens (Gallus gallus domesticus)

Abstract: Black-bone chickens (Gallus gallus domesticus) have become economically valuable, particularly in Southeast Asia as a consequence of popular traditional Chinese medical practices. Chickens with whole body organ darkness are considered to have higher value and are, therefore, more often requested. This research study aimed to investigate the darkness in 34 skeletal muscles of 10 Thai black-bone chickens (five males and five females). The evaluation of muscle darkness was done on two levels: (i) a color chart wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 27 publications
1
12
1
Order By: Relevance
“…Wang et al (2018) found that MITF expression level was highest in the liver of the Muchuan black-boned chickens and MITF promoter polymorphisms affected chicken skin colour. On the contrary, Kriangwanich et al (2021) and Nganvongpanit et al (2020) found that hyperpigmentation was not observed in the liver, which is inconsistent with the present study. Consistently, our lightness value of the liver showed a significant difference between Taihe silky fowl and Chishui silky fowl, but there was no difference in the melanin content.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Wang et al (2018) found that MITF expression level was highest in the liver of the Muchuan black-boned chickens and MITF promoter polymorphisms affected chicken skin colour. On the contrary, Kriangwanich et al (2021) and Nganvongpanit et al (2020) found that hyperpigmentation was not observed in the liver, which is inconsistent with the present study. Consistently, our lightness value of the liver showed a significant difference between Taihe silky fowl and Chishui silky fowl, but there was no difference in the melanin content.…”
Section: Discussioncontrasting
confidence: 99%
“…Recent reports from Kriangwanich et al ( 2021) and Nganvongpanit et al ( 2020)'s study evaluated the muscle darkness and the distribution of melanin pigmentation in 33 Organs of Thai Black-Bone Chickens. They found the dark muscles with the highest degree of darkness mainly included iliotibialis lateralis pars preacetabularis, gastrocnemius, fibularis longus, and puboischiofemoralis pars medialis, and the least dark muscles included serratus profundus, pectoralis, iliotibialis cranialis, flexor cruris lateralis and flexor cruris medialis (Kriangwanich et al 2021). Besides, they also found that the highest and lowest amounts of melanin pigment were noted in the flexor carpi ulnaris and pectoralis.…”
Section: Discussionmentioning
confidence: 93%
“…Histological sections taken from tissue samples of each of these organs were studied. In the muscle tissue samples, the results revealed that the accumulation of melanin pigment was found in the endomysium, perimysium, and epimysium (Kriangwanich et al 2021). The findings revealed that the presence of the melanin pigment in all organs and muscles was not significantly different (P > 0.005) in comparisons made between male and female specimens (Kriangwanich et al 2021;Nganvongpanit et al 2020b).…”
Section: Histological Studymentioning
confidence: 82%
“…Two research studies conducted involving the Thai black-bone chickens aimed to examine the distribution of the melanin pigment in 33 organs (Nganvongpanit et al 2020b) and 34 skeletal muscles (Kriangwanich et al 2021). Thirty-two organs including the brain, spinal cord, sciatic nerve, larynx, trachea, syrinx, lungs, heart, pericardium, aorta, brachial vein, kidney, cloaca, oviduct, testis, gastrocnemius muscle, femur, tongue, esophagus, crop, proventriculus, gizzard, duodenum, jejunum, ileum, cecum, pancreas, liver, gall bladder, omentum, abdominal fat, spleen, and skin were examined in this study.…”
Section: Histological Studymentioning
confidence: 99%
“…Silky fowls (black-bone chickens) are native to some Asian countries and have been consumed as ethno-remedies, owning to the medicinal properties in enhancing immune system, preventing emaciation and remitting conditions such as menstrual abnormalities and postpartum complications [ 9 , 10 ]. They have been domesticated with a long history, and have formed multiple sub-types, such as Taihe, Yanjin, Wumeng, Muchuan and Lueyang black-bone chickens in China, as well as Thai black-bone chickens [ 11 , 12 , 13 ]. In addition to the ethno-pharmacological effects of silky fowl meat, the eggs have also showed some properties that are different from ordinary eggs.…”
Section: Introductionmentioning
confidence: 99%